2022
DOI: 10.3390/microorganisms10061132
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-Based Gene Expression Systems for Lactic Acid Bacteria: A Review

Abstract: Lactic acid bacteria (LAB) play a very vital role in food production, preservation, and as probiotic agents. Some of these species can colonize and survive longer in the gastrointestinal tract (GIT), where their presence is crucially helpful to promote human health. LAB has also been used as a safe and efficient incubator to produce proteins of interest. With the advent of genetic engineering, recombinant LAB have been effectively employed as vectors for delivering therapeutic molecules to mucosal tissues of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…In recent years, numerous studies have shown that LAB exhibit a potential role in delivering biologically active molecules, and therefore promoting the development of mucosal vaccine (Levit et al., 2022 ). To date, various plasmid-based gene expression systems for LAB have been established, and this highly expands the uses of LAB as drug delivery vehicles through genetic modification (Kazi et al., 2022 ). However, using these genetically modified organisms may raise significant public and political concerns.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous studies have shown that LAB exhibit a potential role in delivering biologically active molecules, and therefore promoting the development of mucosal vaccine (Levit et al., 2022 ). To date, various plasmid-based gene expression systems for LAB have been established, and this highly expands the uses of LAB as drug delivery vehicles through genetic modification (Kazi et al., 2022 ). However, using these genetically modified organisms may raise significant public and political concerns.…”
Section: Discussionmentioning
confidence: 99%
“…This study describes the characterization of pTE15 and showed that this large, naturally occurring plasmid (~ 15-kb) replicates via another theta mode mechanism. To our knowledge, although the characteristics of six theta-type plasmids belonged to lactobacilli were description thus for [ 20 – 24 ], but they almost could be classified as class A replicon, which must the plasmid encoded the Rep protein with a related origin of replication and replicate independently of DNA polymerase I [ 25 ]. Therefore, this is the first study demonstrating an unclassified class replicon of theta plasmid in a Lactobacillus species.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the theta-type replication plasmid in lactobacilli were including pLP60 [ 20 ], pRC12 and pRC18 [ 21 ], pRV500 [ 22 ], pREN [ 23 ], and pLJ1 [ 24 ], especially the pRC12, pRC18, pRV500, and pREN belonged to the pUCL287 subfamily. They were class A of theta replicons that must plasmid encoded Rep protein with a related origin of replication and replicate independently of DNA pol I.…”
Section: Introductionmentioning
confidence: 99%
“…These organisms also benefit the administration route via the mucosal route that beneficially induces mucosal and systemic immune responses [176]. LABs, for example, are even more suitable because, in addition to being non-pathogenic, withstanding acidic conditions in the gastrointestinal (GI) system, and protecting nucleic acids, they also exhibit probiotic effects [189]. In addition to these, bacterial derivatives can be used as potentially useful nanocarriers for antigen delivery, some as "bacterial ghosts" that possess the ability to stimulate immune responses as potent as those of live bacteria [190].…”
Section: Archaea Bacteria and Their By-productsmentioning
confidence: 99%